European Union poverty policies. The case of the statistical policy - Pérez-Moreno, Salvador (2006)
A long-lasting difficulty in dealing with the subject of poverty, both in the scientific and political realms, has been the lack of analytical and methodological instruments that facilitate defining, observing and measuring accurately the social dimensions of the phenomenon. Henceforth, it is crucial to develop further indicators in order to design and implement a consistent statistical policy. After examining these issues, this paper analyses the European Union policy on poverty and, especially, the efforts done in the field of statistical policy.